Estudo da extração de óleo de sementes de gergelim (Sesamun indicum L.) empregando os solventes dióxido de carbono supercrítico e n-propano pressurizado - Corso, Marinês Paula (2008)
The vegetable oils extraction has been made mostly through the use of organic solvents through conventional methods. However, due to the search for getting oils with larger quality, without thermal degradation of wished components and safe techniques with contamination reduction by the solvents, a great interest has been demonstrated in the processes development with supercritical fluid in oils and fats industries. Therefore, the current study aimed at to investigate the sesame seeds oil extraction, using the supercritical fluid carbon dioxide and pressurized n-propane. At first, it was made the seeds characterization, and after drying, grind and sifting, they were submitted to the oil extraction with the fluid supercritical CO2 under temperature in different conditions (40, 50 and 60 ºC) and pressure (19, 22 and 25 MPa) and with n-propane in the temperature conditions of 30, 45 and 60 ºC and of pressure of 8, 10 and 12 MPa. The experiments were led through factorial planning with central point of the kind 22 and the processes were compared with the conventional extraction in joint soxhlet with solvent n-hexane. The oil samples were submitted to the analyses of fat acids quantification and differential scanning calorimetry, and the pie was analyzed regarding its protein level. With the data obtained in the extractions were tried the models: Sovová, Tan and Liou and an empiric kinetic model of second order. Through the results it was verified that for the extractions with supercritical CO2 in the studied conditions, more elevated pressures and lower temperatures increased the oil solubility, presenting, both the variables, significant effects (p<0,05). For the extractions with pressurized n-propane, the best solubilities were obtained in higher temperature conditions, independent of pressure. However, statistically, the variable pressure and temperature did not present significant effects about the solubility. The n-propane fluid presented a larger extraction level, with oil larger mass proportion for solvent mass, using conditions of inferior pressure, being, therefore, considerably more advantageous than supercritical CO2. In relation the conventional extraction with n-hexane, it presented a high performance, however with extremely high extraction time if compared to the time used to extraction with pressurized n-propane. The oil extracted even in supercritical conditions with CO2, as well as the extracted with pressurized n-propane presented better oxidative stability, nominated by the time of oxidation induction, than the extracted conventionally with n-hexane. Regarding to the fat acids composition, the oils extracted under the deferential process did not present significant difference. About the protein level of the pie, with pressurized n-propane, it was also possible to obtain a similar pie to the obtained with supercritical CO2, however in a very shorter extraction time. For the extractions accomplished with CO2, Sovová and Souza et al. models were the ones that were better adjusted.